1997
DOI: 10.1002/anie.199707571
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (–)‐Epothilone B: An Extension of the Suzuki Coupling Method and Insights into Structure–Activity Relationships of the Epothilones

Abstract: The cuprates were formed by addition of weighed tablets of Cul or CuCN to the precooled (1 70-210 K) solutions of the organolithium reagents. After complete dissolution of the copper salt (occasionally with slight warming). the freezing point was determined as above. In the case of the amidocuprate [tBu(iPr,N)Cu(CN)Li,], one equivalent of diisopropylamine was added prior to CuCN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
6

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(84 citation statements)
references
References 24 publications
2
76
0
6
Order By: Relevance
“…Recently, the total synthesis of epothilones A and B was accomplished in these laboratories. 10,17 These successes allowed for the synthesis of a variety of epothilone derivatives as well. We have studied the biologic effects of EA, EB, dEA and dEB on prostate cancer cell lines and found that they all inhibit growth potently ( Figure 2 and Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the total synthesis of epothilones A and B was accomplished in these laboratories. 10,17 These successes allowed for the synthesis of a variety of epothilone derivatives as well. We have studied the biologic effects of EA, EB, dEA and dEB on prostate cancer cell lines and found that they all inhibit growth potently ( Figure 2 and Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, synthesis of epothilones is now possible. 10,17,18 This will allow the generation of multiple derivatives, some of which may have increased potency, bypass resistance mechanisms or have decreased toxicity. The similar binding and biologic effects of the very dissimilar taxane and epothilone structures suggests that synthesis of derivative drugs with altered properties will be possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main difference resides in the fact that taxanes are substrates for P-glycoprotein and epothilones are not, and this a b i l i t y t o g e t h e r w i t h e a s e o f f o r m u l a t i o n h a v e b e e n c o n s i d e r e d a d v a n t a g e s f o r overcoming taxane resistance of tumor cells (Wartmann & Altmann, 2002, Cheng et al, 2008. Moreover, whereas the synthesis of paclitaxel relies on 10-deacetylbaccatin III which is available from the needles of various Taxus species , total synthesis of patupilone B has been accomplished (Su et al, 1997). The progress of epothilones in the PC setting has been extensively reviewed (Lee & Kelly, 2009, Lassi & Dawson, 2010, Cheng et al, 2008, Bystricky & Chau, 2011.…”
Section: Epothilonesmentioning
confidence: 99%
“…The clinical successes of paclitaxel have spurred searches for other agents that inhibit the growth of tumors through similar tubulin-based mechanisms of action. More recently discovered compounds with a taxol-like mechanism of action include the discodermolides (4,5), eleutherobins (6), laulimalides (7), and epothilones (8)(9)(10)(11)(12)(13)(14). Despite their supposed common binding site on tubulin assemblies (15)(16)(17)(18), their chemical structures and͞or pharmacological profiles are drastically different.…”
mentioning
confidence: 99%